The Validity of The Statistical Literacy Learning Module - Abdul Wahab; Akhmad Syahid; Junaedi Junaedi (Universitas Negeri Makassar, 2021)
Statistical literacy is the ability to read and interpret data in statistics learning. The main problem raised in this research is how to produce valid statistical literacy learning module tools and instruments. This type of research is quantitative research, the research instruments validated in this study are 14 instruments, namely 5 instruments. Statistical literacy learning tools include (1) Semester Learning Plans, (2) Lecture Units, (3) Books Instructions for Using Modules, (4) Statistical Literacy Module, and (5) Student Activity Sheets, and 9 test and non-test instruments including; (1) Statistics Learning Outcomes Test, and (2) Statistical Literacy Learning Outcomes Test. While the non-test instruments, namely; (1) Assessment sheets for all instruments by expert assessors, (2) Learning module assessment sheets by expert assessors, (3) Lecturer Response Questionnaire Sheet for Statistics Learning, (4) Student Response Questionnaire Sheet for Statistics Learning, (5) Observation Sheet of Statistics Literacy Learning Implementation, (6) Observation Sheet of Lecturers Ability to Manage Statistics Literacy Learning, (7) Observation Sheet of Student Activities on Statistical Literacy Learning, (8) Lecturer Response Questionnaire Sheet Against Statistical Literacy Learning, (9) Student Response Questionnaire Sheet on Statistical Literacy Learning. The results showed that 5 statistical literacy learning instruments and 9 types of test and non-test instruments were declared valid, so that the statistical literacy learning module could be used.